COORDINATES OF POSTAL SERVICES MARKET IN ROMANIA - Cristinel CONSTANTIN (Management & Marketing)
This paper contains a research regarding the actual status of Romanian postal services market both from legislative and economic point of view in the context of EU integration. The main objectives of this research were to identify the position of Romanian postal services among the EU member countries and to analyse the competitive environment on the local market in order to find future development strategies for the local companies. The outcomes of our research show a wrong position of Romanian postal sector both regarding the number of permanent offices and financial results of local competitors. The lateness of structural reforms could be a barrier for the future market liberalisation with serious consequences from the social point of view. In this context, a high implication of authorities is expected in order to ensure the adoption of EU regulation with a minimum of negative effects both for population and service providers.